MRI Assessment of Lumbar Intervertebral Disc Degeneration and its Association with Modic Changes - Jha, Amit; Ghimire, Prasanna; Paudel, Nabin; Jha, Sushmita (Journal of Nepalgunj Medical College, 2024)
Introduction: Low Back Pain is a very common disability affecting millions of people worldwide. Magnetic Resonance Imaging is the preferred tool of investigation in these patients in which commonly encountered findings include lumbar disc degeneration and endplate changes. However, there are few studies exploring a potential relationship between these two findings. Aims: To evaluate whether endplate changes, as described by Modic, are associated with the Pfirrmann grades of disc degeneration. Methods: Magnetic Resonance Imaging scans of the lumbar spine were performed on a consecutive group of 200 patients experiencing low back pain. Disc degeneration was assessed using the Pfirrmann grading system, while endplate changes were categorized according to Modic types. This comprehensive evaluation aimed to identify the relationships between disc degeneration and Modic changes in this patient population. Results: The most commonly affected age groups were those between 40 and 60 years, with a higher prevalence in females. Among 200 patients with disc degeneration, 74 (37%) exhibited Modic changes. The most common type of disc degeneration was Pfirrmann grade III and most common type of Modic change was type II. Non-Modic, Type 1 and Type 2 changes showed significant differences in Pfirrmann grade (p < 0.01). Conclusion: Significant correlation was observed between endplate changes and intervertebral disc degeneration, as demonstrated by imaging findings. This relationship indicates that as disc degeneration worsens, the association between the Pfirrmann and Modic classifications becomes statistically stronger.